2014
DOI: 10.1186/1471-2318-14-99
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and treatment when death is expected in dementia patients in long-term care facilities

Abstract: BackgroundAlthough dementia at the end of life is increasingly being studied, we lack prospective observational data on dying patients. In this study symptoms were observed in patients with dementia in the last days of life.MethodsWhen the elderly care physicians in two Dutch nursing homes expected death within one week, symptoms of (dis)comfort, pain and suffering were observed twice daily. For this the Pain Assessment in Advanced Dementia (PAINAD; range 0–10), Discomfort Scale-Dementia of Alzheimer Type (DS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 47 publications
7
58
1
Order By: Relevance
“…Scores of DS-DAT and PAINAD before death were high, and scores of EOLD-CAD were low (indicating lower comfort) compared with another Dutch study where patients with dementia were observed in the days before death (most patients died of cachexia/dehydration). 13 This contrast does not seem to be attributable to differences in treatments in the last days of life, and confirms earlier findings that death from pneumonia involves a high symptom burden and is less comfortable than death attributed to dehydration after food and fluid intake problems. 6 When death neared, more patients were asleep.…”
Section: Suffering Before Deathsupporting
confidence: 85%
See 1 more Smart Citation
“…Scores of DS-DAT and PAINAD before death were high, and scores of EOLD-CAD were low (indicating lower comfort) compared with another Dutch study where patients with dementia were observed in the days before death (most patients died of cachexia/dehydration). 13 This contrast does not seem to be attributable to differences in treatments in the last days of life, and confirms earlier findings that death from pneumonia involves a high symptom burden and is less comfortable than death attributed to dehydration after food and fluid intake problems. 6 When death neared, more patients were asleep.…”
Section: Suffering Before Deathsupporting
confidence: 85%
“…Although the EOLD-CAD instrument was developed to assess comfort in dying retrospectively, the instrument has been used prospectively with success in patients expected to die, and we used it prospectively for all patients. 13 The observational instrument we applied to observe dyspnea, the RDOS, has been validated, but has not been used before in patients with dementia.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…When people with dementia are transferred to a hospital they often receive intravenous treatment with antibiotics or fluid, or even tube feeding. This treatment increases at the end of life but practice in different countries varies (Klapwijk et al, 2014, Mitchell et al, 2009, and they also vary over time; for example there is a decline in feeding tubes used in USA (Mitchell et al, 2016).…”
Section: Pharmacological Treatment Optionsmentioning
confidence: 99%
“…The research to clarify the patterns of the trajectories of disability deepen discussion about the end‐of‐life in society; people have begun to recognize the importance of thinking about the end of life. There are certain types of symptoms that older adults experience during the end‐of‐life stage; however, the patterns of these symptoms are diverse . Although we can define the patterns of disability during the last stage of life, it is not always possible to predict when that stage will begin .…”
Section: Introductionmentioning
confidence: 99%
“…There are certain types of symptoms that older adults experience during the end-of-life stage; however, the patterns of these symptoms are diverse. 8,9 Although we can define the patterns of disability during the last stage of life, it is not always possible to predict when that stage will begin. 7 This complexity of defining and predicting the end of life within the context of long-term care leads to inescapable end-of-life problems; for example, the provision of futile medical treatments, and unnecessary and unplanned decision-making.…”
Section: Introductionmentioning
confidence: 99%